The Legal Framework of Foster Care in Egypt: A Gender Analysis of Alternative Families and Patrilineal Structures - Fadel, Amira (AUC Knowledge Fountain, 2025)
The thesis explores women’s legal representation and agency over their non-biological children, and how the foster care system in Egypt either reinforces or deconstructs existing gender roles. Hence from a sociological perspective, it accounts for foster and alternative care laws in Egypt and the amendments thereof, to examine social relationships against the backdrop of more conventional, biological families, and kinship relations. In simple terms, studying foster and alternative care laws in Egypt is crucial to grasp how non-biological families are shaped in comparison to the more conventional bonds within biological families and traditional kinship relations, while accounting for the Christian religious minority. This examination can shed light on how these legal frameworks influence the dynamics of support, caregiving, and emotional ties within Egyptian society, offering valuable insights into how the subject is produced and the complex interplay between legal structures and social relationships, with gender, law, and religion being at the core of the analysis.